A Facile One‐Pot Synthesis of Hierarchically Organized Carbon/TiO2 Monoliths with Ordered Mesopores. Issue 2 (18th February 2021) - Schoiber, Jürgen; Koczwara, Christian; Rumswinkel, Simon; Whitmore, Lawrence; Prehal, Christian; Putz, Florian; Elsaesser, Michael S.; Paris, Oskar; Hüsing, Nicola
Abstract: Sol–gel processing combined with soft templating and gelation‐induced phase separation is very sensitive to the precursor sol composition. In this work we present a straightforward synthesis towards hierarchically structured, macroporous carbon/titania monoliths with ordered mesopores derived from resorcinol/formaldehyde monoliths and a glycolated titanium precursor. We demonstrate the influence of various reaction solvents, where diol‐based media and the proportion of the catalyst seem to be essential in controlling spinodal decomposition, obtaining similar monolithic structures under different synthesis conditions. Based on these observations, we further homogeneously incorporated TiO2 into the carbon structure by an in situ synthesis approach, obtaining structural features similar to pure carbon materials with surface areas of about 400 m 2 g −1, periodically arranged mesopores with a mean distance of 10–11 nm and cellular macroporosity. Abstract : Bringing order : C/TiO2 monolithic composite materials with ordered pore structure are synthesized by a soft chemical (sol‐gel) approach. Organic diol‐based reaction solvents are indispensable for obtaining the desired carbon morphology alongside the acidic catalyst concentration. To introduce TiO2 while retaining the carbon structure, the Ti‐alkoxide precursor, namely ethylene glycol modified titanate, was introduced in the sol‐gel synthesis.